Parliamentary Perspectives and Oversight Functions in the Best Practices of the Dutch Tweede Kamer: A Case Study of the 2014 e-KTP Corruption - Dyandra Natha Nararya; Naifa Dwinka Wardana; Siti Lutfiya Munzilal Wahyu; Tsurayyaa Zahira Surfiyanto; Rwanda Darigha Ananty (Yayasan Taslim Madayana Indonesia, 2026)
Background. The oversight function of the Indonesian House of Representatives (DPR) is vital for maintaining transparency and accountability in governance. However, the 2014 e-KTP corruption case exposed serious weaknesses in this oversight role, particularly the misuse of the right of inquiry for political purposes, undermining its credibility and effectiveness. Purpose. The study aims to analyze the weaknesses in Indonesia’s legislative oversight system, as exemplified by the e-KTP case, and to propose improved mechanisms by learning from Dutch parliamentary practices. The goal is to develop a more objective, transparent, and independent oversight model suited to Indonesia’s context. Method. This research uses a qualitative, comparative approach, analyzing the 2014 e-KTP case as a key example of oversight failure. It then conducts a comparative study of the Dutch parliamentary system to identify oversight practices that can be adapted for Indonesia. The study involves document analysis, case review, and institutional comparison. Results. The study finds that Indonesia’s current oversight mechanisms are prone to political misuse and lack transparency. It recommends adopting features of the Dutch system—such as independent oversight bodies, open access to reports, and transparent procedures—while adjusting them to fit Indonesia’s political and legal environment to strengthen democratic accountability. Conclusion. The DPR's oversight function has been undermined by political misuse and unclear regulations, as seen in the e-KTP case. To restore public trust and ensure effective oversight, reforms are needed—drawing on Dutch best practices—to create a transparent, objective, and participatory system supported by clear legal frameworks.